Anticoagulant treatment for subsegmental pulmonary embolism - Yoo, Hugo Hyung Bok [UNESP]; Queluz, Thais Helena Abrahão Thomaz [UNESP]; El Dib, Regina [UNESP] (Wiley-Blackwell, 2014)
BackgroundAcute pulmonary embolism (PE) is a common cause of death, accounting for 50,000 to 200,000 deaths annually. It is the third most common cause of mortality among the cardiovascular diseases, after coronary artery disease and stroke.The advent of multi-detector computed tomographic pulmonary angiography (CTPA) has allowed better assessment of PE regarding visualisation of the peripheral pulmonary arteries, increasing its rate of diagnosis. More cases of peripheral PEs, such as isolated subsegmental PE (SSPE) and incidental PE, have thereby been identified. These two conditions are usually found in patients with few or none of the classic PE symptoms such as haemoptysis or pleuritic pain, acute dyspnoea or circulatory collapse. However, in patients with reduced cardio-pulmonary (C/P) reserve the classic PE symptoms can be found with isolated SSPEs. Incidental SSPE is found casually in asymptomatic patients, usually by diagnostic imaging performed for other reasons (for example routine CT for cancer staging in oncologic patients).Traditionally, all PEs are anticoagulated in a similar manner independent of the location, number and size of the thrombi. It has been suggested that many patients with SSPE may be treated without benefit, increasing adverse events by possible unnecessary use of anticoagulants.Patients with isolated SSPE or incidental PE may have a more benign clinical presentation compared with those with proximal PEs. However, the clinical significance in patients and their prognosis have to be studied to evaluate whether anticoagulation therapy is required.ObjectivesTo assess the effectiveness and safety of anticoagulation therapy versus no intervention in patients with isolated subsegmental pulmonary embolism (SSPE) or incidental SSPE.Search methodsThe Cochrane Peripheral Vascular Diseases Group Trials Search Co-ordinator searched the Specialised Register (last searched October 2013) and CENTRAL (2013, Issue 9). MEDLINE, EMBASE, LILACS and clinical trials databases were also searched (October 2013).Selection criteriaRandomised controlled trials of anticoagulation therapy versus no intervention in patients with SSPE or incidental SSPE.Data collection and analysisTwo review authors inspected all citations to ensure reliable selection. We planned for two review authors to independently extract data and to assess the methodological quality of identified trials using the criteria recommended in the Cochrane Handbook for Systematic Reviews of Interventions.Main resultsNo studies were identified that met the inclusion criteria.Authors' conclusionsThere is no randomised controlled trial evidence for the effectiveness and safety of anticoagulation therapy versus no intervention in patients with isolated subsegmental pulmonary embolism (SSPE) or incidental SSPE, and therefore we can not draw any conclusions. Well-conducted research is required before informed practice decisions can be made.